Analysing the mechanical behavior of A6061/SiC/B4C/Flyash composite fabricated through stir casting - Subramani, N; Krishnan, R (International Journal of Engineering and Technology, 2018)
Alloys of Aluminium are prominently used in automobiles, aerospace and ship building industries because of their high strength to weight ratio. The aim of this work is to manufacture the particulate reinforced metal matrix composite (PRMMC) materials by using Aluminium 6061 and reinforcing Boron Carbide, particles of silicon and fly ash. The study helps to fabricate an optimized composite material through the best methodology which is identified at the end of the experimental studies which is going to be carried out. This study helps the current researches carried on the nano-composite materials and PRMMC. In this paper, the Aluminium 6061 and its reinforcements are discussed and it gives a methodology to select the optimized method. The specimens fabricated by stir casting are analyzed and categorized according to their mechanical behavior by conducting mechanical tests. The Micro-structure of the specimen is examined by scanning electron microscopy (SEM) and spectrum analysis is done to the reinforcement distribution percentage.